2019
DOI: 10.1186/s12966-019-0845-y
|View full text |Cite
|
Sign up to set email alerts
|

Picky eating in an obesity intervention for preschool-aged children – what role does it play, and does the measurement instrument matter?

Abstract: Introduction Research on picky eating in childhood obesity treatment is limited and inconsistent, with various instruments and questions used. This study examines the role of picky eating in a randomized controlled obesity intervention for preschoolers using subscales from two instruments: The Child Eating Behavior Questionnaire (CEBQ) and the Lifestyle Behavior Checklist (LBC). Method The study includes 130 children (mean age 5.2 years (SD 0.7), 54% girls, mean Body Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 26 publications
0
35
1
2
Order By: Relevance
“…Specifically, on the occasions where fish intake was reported, 20% was contributed by fried fish sticks/fish burgers, which do not align with recommendations for healthy choices, both in terms of fish species and cooking methods. Children with obesity may also be more likely to exhibit fussy eating patterns and unwilling to consume unfamiliar foods, as a result, parents may offer foods based on children's tastes and preferences 47 . In addition, common barriers including cost of fish, accessibility, the lack of inspiration or cooking skills and differences in cultural background remain to be important determinants of fish consumption 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, on the occasions where fish intake was reported, 20% was contributed by fried fish sticks/fish burgers, which do not align with recommendations for healthy choices, both in terms of fish species and cooking methods. Children with obesity may also be more likely to exhibit fussy eating patterns and unwilling to consume unfamiliar foods, as a result, parents may offer foods based on children's tastes and preferences 47 . In addition, common barriers including cost of fish, accessibility, the lack of inspiration or cooking skills and differences in cultural background remain to be important determinants of fish consumption 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Порушення ХП діагностувалося, якщо середнє значення набраних балів перевищувало середні показники при обмежувальній, емоціогенній і екстернальній ХП у пацієнтів з нормальною вагою, що становлять 2,4; 1,8 і 2,7 відповідно. Ступінь порушення ХП виражався в такий спосіб: «дуже низький» (0-19 %); «низький» (20-39 %); «середній» (40-59 %); «підвищений» (60-79 %); «високий» (80-100 %) [6,[14][15][16].…”
Section: матеріали та методиunclassified
“…Finally, we hypothesized that higher baseline levels of parental depression would be associated with obesity‐related child eating and parental feeding behaviors. In previous analyses of the ML study, no significant changes in feeding practices or child eating behaviors were found after treatment 17,18 . Thus, in this study, only baseline reports of feeding and eating behaviors were used to analyze the associations with parental depression.…”
Section: Introductionmentioning
confidence: 96%
“…In previous analyses of the ML study, no significant changes in feeding practices or child eating behaviors were found after treatment. 17,18 Thus, in this study, only baseline reports of feeding and eating behaviors were used to analyze the associations with parental depression.…”
mentioning
confidence: 99%